Stakeholders Participation in School Development Case Studies from Rural Tamil Nadu - Ravi, R. Venkata; Dharmaraj, P.; Ramesh, S. (JOURNAL OF INDIAN EDUCATION, 2021)
The sustainable development in rural area depends on the availability of infrastructure facilities and its utilisation. The infrastructure facilities include physical, economic and social infrastructure. The social infrastructure includes assets that facilitate social services such as schools, universities, hospitals, and community housing. In the contemporary educational system, many stakeholders are playing a crucial role in the development of local community and also for the school development. The school development covers the aspects such as management of infrastructure facilities in the schools, teachers and other staff, academic transactions and co-curricular activities. These core factors are most important for enabling the students for their future course of action. A research was undertaken in the Dindigul district of Tamil Nadu to study the stakeholders’ roles and contribution in the process of school development. An attempt has been made in this paper to present the case studies on the best practices by various stakeholder institutions in the context of School Development and Management (SDM).